PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN (Studi terhadap karyawan PT. PLN (Persero) Distribusi Jawa Timur) - Dwi Putra, Hafiidh Sancoko; Nimran, Umar; Hamid, Djamhur (Profit: Jurnal Adminsitrasi Bisnis, 2015)
The kind of research this is explanatory research, the goal of this research is to analyze and explain: (1) Transformational Leadership influence significantly to job satisfaction, (2) Job Characteristics influence significantly to job satisfaction, (3) Transformational Leadership influence significantly to the performance of employees, (4) Job Characteristics impact Employee Performance, significantly to (5) job satisfaction influence significantly to the performance of employees. The population of this research as many as 212 people permanent employees of PT.PLN (Persero) of East Java, the withdrawal Distribution samples using Simple Random Sampling techniques so that the retrieved sample as many as 68 people permanent employees of PT.PLN (Persero) of East Java, Distribution data collection using the questionnaire. This research result is: ( 1 ) leadership transformational influence significantly to job satisfaction ( 2 ) characteristic of job satisfaction, influential significantly to work ( 3 ) leadership transformational significant impact on the performance employees ( 4 ) characteristic work influential insignificant against employees performance ( 5 ) complacence influential insignificant work on the performance of employees.Â Â